2020
DOI: 10.3389/fimmu.2020.00233
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Let-7f in Bone Marrow-Derived Mesenchymal Stem Cells Triggers Treg/Th17 Imbalance in Patients With Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) patients exist an imbalance between regulatory T (Treg) and T helper 17 cells (Th17), which might be contributed by defective immune regulation of bone marrow derived mesenchymal stem cells (BM-MSCs) from SLE patients. Our microRNA array analysis showed markedly down-regulated expression levels of microRNA let-7f in BM-MSCs from SLE patients compared to those from normal controls (NOR). To explore the role of let-7f in the disease pathogenesis, we showed that expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have been widely used in the clinical setting, not only for autoimmune diseases [ 9 , 10 ] but also for infectious diseases [ 11 13 ], and their safety and effectiveness have been well elucidated. Umbilical cord mesenchymal stem cells (hUC-MSCs), a kind of MSC, can be easily obtained and expanded in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have been widely used in the clinical setting, not only for autoimmune diseases [ 9 , 10 ] but also for infectious diseases [ 11 13 ], and their safety and effectiveness have been well elucidated. Umbilical cord mesenchymal stem cells (hUC-MSCs), a kind of MSC, can be easily obtained and expanded in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have been widely used for solution of clinical issues, not only just in autoimmune diseases [8,9], but also in infectious diseases [10][11][12], and the safety and effectiveness have been well elucidated. Umbilical cord mesenchymal stem cells (hUC-MSCs), as one kind of MSCs, can be easily obtained and expansion in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…T-cell immunosuppressive effects of MSCs in controlling Th17 and Th1 depend on the doses of MSC introduction to the inflammatory milieu in addition to the presence of other immune cells and the immune cells released soluble factor [17]. Other studies revealed that early MSCs administration into the autoimmune developing animal model might ameliorate those severity diseases, whereas later administration did not improve the imbalance of Th17 cells [18], [19]. To explore the potency of MSCs in controlling Th17 and Th1, we used in vitro model of the coculture of MSCs and PBMCs from SLE patients for 72 h of incubation with several doses.…”
Section: Discussionmentioning
confidence: 99%